Fe 50 Ni 50 synthesized by high energy ball milling: A systematic study using X-ray diffraction, EXAFS and Mössbauer methods - Rodríguez V.A.P. (2019)
Fe 50 Ni 50 alloy powder was prepared by milling the 1:1 stoichiometric mixture of Fe and Ni high purity elements using high energy vibrational ball-mill. Final powdered material was obtained directly after 30 h of milling process and the Rietveld analysis of the X-ray diffraction pattern of the sample reveals the presence of two Fe–Ni phases: the disordered ?–(Fe 45 Ni 55 ) alloy, with 91% of total fraction of the material (Fe–Ni solid solution plus grain boundary regions) and the chemically-ordered FeNi phase (9%), with L1 0 tetragonal structure. Average grain sizes of these Fe–Ni phases are respectively 60 nm and 20 nm. Results of extended X-ray absorption fine structure of Ni and Fe as well as 57 Fe Mössbauer spectroscopy also suggest the presence of atomically ordered FeNi phase. Mössbauer data have also shown that both Fe–Ni phases are magnetically ordered at room temperature. Our results indicate that high energy milling method can simulate extreme conditions of sample preparation required for the formation of the T-FeNi phase. © 2019